Environmental impacts of international business and entrepreneurship: do green and innovation technologies play significant roles? - Omri, Anis; Al-Qasir, Mohammed (Frontiers in Sustainability, 2025)
This study examines the pivotal roles of entrepreneurship and international business in promoting environmental sustainability, with a focus on the contributions of green and innovative technologies. Grounded in the context of Saudi Arabia from 2000 to 2022. The analysis reveals that both entrepreneurship and international business currently exert negative environmental pressures, notably through rising CO₂ emissions. However, integrating green and technological innovation significantly alters these dynamics. Green technologies help mitigate the environmental impact of entrepreneurship and enhance overall environmental performance in international business, particularly when their adoption exceeds key threshold levels. Similarly, innovative technologies strengthen entrepreneurship’s ability to reduce emissions, though their moderating effect on international business is more nuanced. These findings underscore the conditional nature of economic–environmental linkages and highlight the transformative potential of technology in steering economies toward sustainable pathways. The results offer valuable insights for policymakers, businesses, and stakeholders committed to advancing sustainable development through innovation and environmentally responsible strategies.